A study on a faulty design defects in newly completed public hospital buildings in Kelantan / Nor Syamimi Mohd Shafuldin - Mohd Shafuldin, Nor Syamimi (2015)
Design is very important to the building performance and also gives huge impact on the building maintenance. However, error in designing the building will cause the appearance of defects on the building itself. Nowadays, there are always having many issues on a poor design on the newly completed hospital buildings which is keeps reporting in media especially in the government or public sectors. This research study is focused on the issue of poor design in newly completed public hospital buildings. Multiple case studies in Kelantan Darul Naim had been adopted which is Hospital Universiti Sains Malaysia, Hospital Raja Perempuan Zainab II, and Hospital Pakar Tanah Merah. Finding revealed that the design defects that are caused by the faulty design will give lack of satisfaction level to the users of the public hospital buildings. Therefore, this research study will discuss on the types of design defects in newly completed public hospital buildings and the main factors that affects the newly completed building of public hospitals.